STRATEGI PEMASARAN SEBAGAI FAKTOR PENENTU KEBERHASILAN PRODUK TABUNGAN DAN PEMBIAYAAN di PT BPRS HAJI MISKIN - Andini Amalia Putri SW; Mia lasmi Wardiyah (Jurnal Riset Multidisiplin Edukasi, 2025)
This study examines the marketing strategies for savings and financing products at PT. BPRS Haji Miskin, a sharia rural bank in Indonesia. Using a descriptive qualitative approach, data were collected through interviews, observation, and documentation involving management and marketing staff. The findings reveal that effective market segmentation, product development tailored to local needs and sharia principles, and ethical promotional strategies are key to attracting new customers and retaining existing ones. The bank’s educational and personal approach helps improve public understanding of sharia financial products. However, challenges remain, including low financial literacy and limited marketing resources. The study highlights the need for continuous innovation and digital technology adoption to expand market reach and enhance competitiveness. The results are expected to enrich the literature on Islamic banking marketing and provide practical recommendations for developing more effective and sustainable marketing strategies at PT. BPRS Haji Miskin.